2008
DOI: 10.1166/jnn.2008.280
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Embedded Nanocrystalline Titania Sorbent for 99Mo-99mTc Generator

Abstract: A new sorbent material, polymer embedded nano crystalline titania (Titanium Polymer-TiP) has been developed, from titanium (IV) chloride and isopropyl alcohol, for the adsorption of 99Mo, which is a precursor to 99mTc, a workhorse in radio-pharmaceuticals. The infrared absorption spectra of the TiP showed peaks corresponding to Ti-O groups. X-ray diffraction pattern of the adsorbent corresponded to rutile TiO2. The surface area of this polymer was 30 m2/g with an average pore size of 40 nm. The average crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Nanomaterial based sorbents which have very high sorption capacity per unit mass owing to high surface area-to-volume ratio and intrinsic surface reactivity, are the most promising a Activity was measured after allowing the irradiated target to cool for 1 day Fig. 7 Recovery of Ge from the used TiP column materials as column matrices and TiP developed and explored by us earlier [24,25] [30]. Except 71 Ge (t = 11.2 days), the other activated Ge radionuclides are short-lived.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nanomaterial based sorbents which have very high sorption capacity per unit mass owing to high surface area-to-volume ratio and intrinsic surface reactivity, are the most promising a Activity was measured after allowing the irradiated target to cool for 1 day Fig. 7 Recovery of Ge from the used TiP column materials as column matrices and TiP developed and explored by us earlier [24,25] [30]. Except 71 Ge (t = 11.2 days), the other activated Ge radionuclides are short-lived.…”
Section: Discussionmentioning
confidence: 99%
“…TiP was synthesized in situ by the reaction of TiCl 4 and isopropyl alcohol in 2:1 stoichiometric ratio, as reported by us earlier [24].…”
Section: Synthesis Of Tipmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a new adsorbent material having higher adsorption capacity for Mo-99 (200 mg/g of PZC). Scientist in Bhabha Atomic Research Centre (BARC) has also reported about nano-zirconia, titania, and γ-alumina[678] adsorbent material for adsorption of molybdenum with higher adsorption capacities for preparing Mo-99/Tc-99m column generator.…”
Section: Introductionmentioning
confidence: 99%